Uma viagem cartográfica entre encontrosformação com licenciandos : uma experimentação no Instituto Federal do Espírito Santo - Moreira, Priscila dos Santos (2019)
The research aims at monitoring the cartographic strokes along with the Math graduates from the Espírito Santo Federal Institute (Ifes) between the lines of desire and (de)(re)territorializing processes, in order to propagate the multiple possibilities of a body in the formation-meetings with (future) Teachers through a Supervised Practice. The dissertation discusses what the faculty members are able to do during formation meetings processes, going through the field known as “Teachers’ training (formation)” and questioning serializations such as, “initial formation” and “Teachers’ continuing training” regarding the entanglement with other ways of thinking-building this area, based on the Gilles Deleuze and Félix Guattari philosophy of difference. The work maps the college degree territory monitoring the conversation networks with agents belonging to Rectory and the city of Vitória campus and, mainly, with the graduates through the collective meetings-lessons in the III Supervised Practice (high school) and individual talks between the researcher and pupils (in which field diaries and voice recorders were used) and the analysis of individual reports produced by those students. It is observed that the outside assessments, for instance, “Program of Elementary Education Evaluation in the state of Espírito Santo” (Paebes) and “National High School Evaluation” (Enem) stiffen and (re)territorialize the high school ruler curriculum (concept of a standard, single curriculum that follows a certain logics) in Espírito Santo. The work narrates, from the conversations with the graduates, the high school teacher condition placed in the edge between a ruler-curriculum that demands a performance focused on the external evaluations in an abstract machine that organizes dominant assertions when a utilitarianism is established within education, which, through power equipment, imprisons elementary education teachers and students and college degree ones inside faces. It associates the “prompt questions and answers (cliché)” pattern and the neotechnicist traditional education with the recognition and sad affection, in complex over codifying capitalistic machine gears able to create a stagnation of the thinking flows. The work stands out zigzag movements, in which stiffen and slippery lines are engendered among (de)(re) territorialization and generate sparks of possibilities before the erasures striated spaces of the education merchandise logics. It highlights that, even though the escape lines are not seen as dominant in the curricular moves, the desiring lines were (co)engendered enabling the destructuring of the ruler-curriculum and the curricula-difference invention through gaps. It also emphasizes what a lesson, the Supervised Practice, a body of singular passengers can do in order to organize good meetings with the graduates. The paper proposes the fracture of the accent in “é” (representation, identity, face, immutable answers, solution for the “true questions-answers” pair) to compose with the “e” among the several formation-meetings between “supervised-college degree practices and schools” like practical policies. By way of conclusion, the work suggests the enlargement of the space-time used for collective conversations concerning the experience lived at school, in the Supervised Practice, in order to invent the bird university degrees that are able to resound the inventions of other trips based on the discussion of “immovable model-trip” repetition of a teaching-face, the illusion of the homogeneous passengers and exceptional and uniform destinations that stiffen the formation-meetings processes with (future) Teachers.